Statistics and clinical practice - Doroszewski, Jan Witold; Bobrowski, Leon; Górski, A; Marubini, E (Nakladatel není známý, 1998)
Abstracts of papers delivered at the seminar held on the 24-27 of June, 1998 which discussed statistics, biocybernetics and biomedical engineering in clinical cractice. Intended for professionals.
Keywords: využití lékařské informatiky; International Cooperation; mezinárodní spolupráce; biomedicínské inženýrství; biomedicínské technologie; Biomedical Technology; lékařská informatika; Congresses as Topic; Medical Informatics Applications; Clinical Medicine; statistika, zdravotnická statistika; kongresy jako téma; klinické lékařství